Optimalisasi Bauran Promosi Dalam Meningkatkan Nilai Penjualan Kain Tenun Songket Pada Galeri Tenun Desa Setanggor Lombok Tengah - Dewi Rispawati (Departement of Mathematics Education, 2024)
This research is entitled Optimizing the Promotion Mix in Increasing the Sales Value of Songket Woven Fabrics at the Setanggor Village Weaving Gallery, Central Lombok Regency which aims to increase the Promotion Mix that will be used in increasing sales of Songket Woven Fabrics at the Setanggor Village Weaving Gallery, Central Lombok. This research uses descriptive methods with a qualitative approach. In analyzing this research using triangulation techniques through data validity checks. The types of data in this study are qualitative data and quantitative data. The data sources in this study are primary data and secondary data. The results of the research on Optimizing the Promotion Mix in Increasing the Sales Value of Songket Woven Fabrics at the Setanggor Village Weaving Gallery, Central Lombok, namely by using a promotion mix including: direct marketing, sales promotion, personal selling, public relations, and mass selling. By optimizing the promotion mix in marketing the Setanggor Village Songket Woven Fabric products so that they can be known by the public to foreign countries so as to increase the sales value of Songket Woven Fabric at the Setanggor Village Weaving Gallery, Central Lombok.